Inpatient detection of cardiac-inherited disease: the impact of improving family history taking. Issue 1 (16th February 2016) - Waddell-Smith, Kathryn E; Donoghue, Tom; Oates, Stephanie; Graham, Amanda; Crawford, Jackie; Stiles, Martin K; Aitken, Andrew; Skinner, Jonathan R
Abstract : Objectives: 'Idiopathic' cardiac conditions such as dilated cardiomyopathy (DCM) and resuscitated sudden cardiac death (RSCD) may be familial. We suspected that inpatient cardiology services fail to recognise this. Our objective was to compare diagnostic value of family histories recorded by inpatient cardiology teams with a multigenerational family tree obtained by specially trained allied professionals. Methods: 2 experienced cardiology nurses working in 2 tertiary adult cardiac units were trained in cardiac-inherited diseases and family history (FHx) taking, and established as regional coordinators for a National Cardiac Inherited Disease Registry. Over 6 months they sought 'idiopathic' cardiology inpatients with conditions with a possible familial basis, reviewed the FHx in the clinical records and pursued a minimum 3-generation family tree for syncope, young sudden death and cardiac disease (full FHx). Results: 37 patients (22 males) were selected: mean age 51 years (range 15–79). Admission presentations included (idiopathic) RSCD (14), dyspnoea or heart failure (11), ventricular tachycardia (2), other (10). 3 patients had already volunteered their familial diagnosis to the admitting team. FHx was incompletely elicited in 17 (46%) and absent in 20 (54%). 29 patients (78%) provided a full FHx to the coordinator; 12 of which (41%) were strongly consistent with a diagnosis of a cardiac-inherited disease (DCM 7, hypertrophic cardiomyopathy 3, long QT 1, left ventricular non-compaction 1). Overall, a familial diagnostic rate rose from 3/37(8%) to 12/37 (32%). Conclusions: Adult cardiology inpatient teams are poor at recording FHx and need to be reminded of its powerful diagnostic value.